What works, how and in which contexts when using digital health to support parents/carers to implement intensive speech and language therapy at home for children with speech sound disorder? A realist review - Leafe, Naomi; Pagnamenta, Emma; Taggart, Laurence; Donnelly, Mark; Hassiotis, Angela; Titterington, Jill (PloS one, 2025)
Digital health solutions to support parent-implemented interventions alongside direct speech and language therapist (SLT) input could help increase intervention intensity for children with speech sound disorder (SSD) to meet evidence-based recommendations. This realist review explores the factors which could make intensive parent-implemented digital interventions for children with SSD effective, and how this complex intervention might work in different contexts. Realist review methodology was adopted to explore what works, why, how, for which parents/carers, and in what circumstances. Realist methods aimed to understand the active ingredients, contexts, and associated outcomes of this complex intervention. Preliminary theories were developed to describe how and why digital parent-implemented interventions work for children with SSD. Data was extracted from 43 papers to test and refine preliminary theories. Behaviour change theories were used to explain how the intervention works in practice. A set of 20 explanatory theories were developed to depict how and why digital parent-implemented interventions work in different contexts. Theories covered five areas: child-participation; the child-parent-SLT dynamic; parent-training; partnership and collaboration; intervention intensity. The theories describe mechanisms of the intervention and how these are responded to in different situations. Findings highlight the importance of intensive intervention for children with SSD. This realist review adds new in-depth insight into how digital parent-implemented interventions work, for whom, and why. This new understanding has potential to support future successful digital parent-implemented interventions and increase intervention intensity for children with SSD globally. Implications for services and the potential of emerging digital health approaches to promote parent-implemented interventions are discussed.